2008
DOI: 10.1042/bc20070086
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐3‐truncated type 1 inositol 1,4,5‐trisphosphate receptor enhances intracellular Ca2+ leak and disturbs Ca2+ signalling

Abstract: Background information-The IP 3 R (inositol 1,4,5-trisphosphate receptor) is a tetrameric channel that accounts for a large part of the intracellular Ca 2+ release in virtually all cell types. We have previously demonstrated that caspase-3-mediated cleavage of IP 3 R1 during cell death generates a C-terminal fragment of 95 kDa comprising the complete channel domain. Expression of this truncated IP 3 R increases the cellular sensitivity to apoptotic stimuli, and it was postulated to be a constitutively active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 52 publications
(59 reference statements)
6
42
0
Order By: Relevance
“…undergoes proteolysis in a manner consistent with previous studies in DT40 cells and several other cell types (22)(23)(24)(25). More importantly, our experiments suggest that during apoptosis, IP 3 R1 is cleaved into two overlapping N-terminal fragments encompassing the suppressor domain, the ligand-binding domain, and most of the coupling domain and a C-terminal fragment containing the channel domain and the cytosolic tail.…”
Section: Characterizing Ip 3 R1 Fragmentation Patterns During Apoptosis-supporting
confidence: 74%
See 4 more Smart Citations
“…undergoes proteolysis in a manner consistent with previous studies in DT40 cells and several other cell types (22)(23)(24)(25). More importantly, our experiments suggest that during apoptosis, IP 3 R1 is cleaved into two overlapping N-terminal fragments encompassing the suppressor domain, the ligand-binding domain, and most of the coupling domain and a C-terminal fragment containing the channel domain and the cytosolic tail.…”
Section: Characterizing Ip 3 R1 Fragmentation Patterns During Apoptosis-supporting
confidence: 74%
“…7E. Previous studies showed that transient expression of the C-terminal 95-kDa-fragment resulted in a modest depletion of ER stores (22,27,30). However, examination of resting Ca 2ϩ levels and the content of intracellular Ca 2ϩ stores, as judged by the rate and magnitude of cyclopiazonic acid -induced Ca 2ϩ release, showed no significant difference between these cell lines, expressing channel-only fragments and IP 3 R1 cells or FIGURE 7.…”
Section: Characterizing Ip 3 R1 Fragmentation Patterns During Apoptosis-mentioning
confidence: 97%
See 3 more Smart Citations